Edukasi Pencegahan Stunting Sebagai Upaya Meningkatkan Kesadaran Orang Tua Terhadap Gizi Anak Di Desa Keling Kabupaten Kediri - Zuraidah Zuraidah; Rizky Maulana; Ika Aryanti Anugrah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
This research focuses on preventing stunting as an effort to increase parents' awareness of children's nutrition. Stunting is a condition that results in chronic malnutrition, slow growth combined with weight and height that do not increase, so that stunting in babies and toddlers can be used as a sign of maternal and child health. The aim of this community service activity is to increase parents' understanding and knowledge in preventing stunting in order to prevent an increase in the number of children affected by stunting. The technique used is a socialization technique which includes lectures and distribution of leaflets. The method used is the one group pre-test and post-test experimental method. A pretest was given to participants at the start to find out parents' knowledge about stunting. A post-test was given to each participant at the end as part of the evaluation process with the aim of identifying participants after socializing their understanding of stunting. The research results showed that there was an increase in parents' knowledge about stunting after the socialization was carried out.